Warehouse National Police Commission: Limited Authority And Non Maximum Contribution - Edi Saputra Hasibuan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
In every institution, it should have a code of ethics and rules that reference an action that can be taken, in this case, of course, the Indonesian National Police also have their own code of ethics, regarding which there is an institutional figure who basically has the duty to supervise and interfere with the determination of Police policies that can bring this institution to a better direction, The National Police Commission (Kompolnas) was formed with the aim of being able to provide direction and supervision to the National Police institutionally, also highlighting any behavior of members that are not in accordance with procedures so that there is no more irregularities that can damage the image of the National Police itself, but in practice often this one commission is limited in movement, even in some major cases that occur in the National Police often do not present the National Police Commission, this is a question, regarding what are the obstacles for Kompolnas in carrying out their functions, so that this institution cannot work optimally